2017
DOI: 10.1186/s12711-017-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies and genomic prediction of breeding values for calving performance and body conformation traits in Holstein cattle

Abstract: Background: Our aim was to identify genomic regions via genome-wide association studies (GWAS) to improve the predictability of genetic merit in Holsteins for 10 calving and 28 body conformation traits. Animals were genotyped using the Illumina Bovine 50 K BeadChip and imputed to the Illumina BovineHD BeadChip (HD). GWAS were performed on 601,717 real and imputed single nucleotide polymorphism (SNP) genotypes using a single-SNP mixed linear model on 4841 Holstein bulls with breeding value predictions and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 72 publications
4
57
1
4
Order By: Relevance
“…has been associated with teat length 23 , and our fine-mapping showed that it had an effect on six type traits (including teat length, fore udder attachment, front teat placement, rear teat placement, rear udder height, and final score), with PPC being ≥ 0.95 for all those traits. Abo-Ismail et al…”
Section: Candidate Genesmentioning
confidence: 75%
See 2 more Smart Citations
“…has been associated with teat length 23 , and our fine-mapping showed that it had an effect on six type traits (including teat length, fore udder attachment, front teat placement, rear teat placement, rear udder height, and final score), with PPC being ≥ 0.95 for all those traits. Abo-Ismail et al…”
Section: Candidate Genesmentioning
confidence: 75%
“…reported CCND2 was associated with stature 23 . Our fine-mapping results determined its association with four type traits (PPC >0.95 for body depth, rump width, and stature).…”
Section: Candidate Genesmentioning
confidence: 91%
See 1 more Smart Citation
“…Genetic selection offers a sustainable tool to improve dairy cattle farming via the selection of animals with reduced susceptibility toward diseases, which in turn results in improved periparturient health. Until now, association and linkage studies have revealed promising results concerning bovine chromosome 18 (BTA18) and performance traits (Mao et al, 2016;Abo-Ismail et al, 2017;Müller et al, 2017;Wu et al, 2017). Concerning udder health, Kühn et al (2008) showed that the prediction of half-sib heifers with a high or low SCS was possible through marker-assisted selection regarding a confirmed QTL for SCS in the telomeric region of BTA18.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic selection offers a sustainable tool to select animals with decreased susceptibility towards postpartum diseases. Several groups have reported promising associations between Bos taurus autosome 18 (BTA 18) and performance traits [26][27][28][29]. Our own studies revealed differing immune competence of primary mammary epithelial cells (MEC) originating from two BTA 18 haplotypes: half sib uniparous cows inheriting an alternative haplotype of a confirmed quantitative trait locus (QTL) for somatic cell score (SCS) in the telomeric region of BTA 18 showed different somatic cell scores in vivo [30].…”
Section: Several Studies Have Reported Correlations Between Differentmentioning
confidence: 99%